Features of the extreme events observed in an all-solid-state laser with a saturable absorber - Bonazzola, Carlos Raúl (2015)
Extreme events in the form of pulses of extraordinary intensity (sometimes also called optical rogue waves) are easily observed in the chaotic regime of an all-solid-state laser with a saturable absorber if the Fresnel number of the cavity is high. This result suggests that the nonlinear interaction among transverse modes is an essential ingredient in the formation of extreme events in this type of laser, but there is no theoretical description of the phenomenon yet. We report here a set of experimental results on the regularities of these extreme events in order to provide a basis for the development of such a description. Among these results, we point out here (i) the decay of the correlation across the transversal section of the laser beam, and (ii) the appearance of extreme events even if the time elapsed since the previous pulse is relatively short (in terms of the average interpulse time interval), which indicates the existence of some unknown mechanism of energy storage. We hypothesize that this mechanism is related to the imperfect depletion of the gain by some of the transversal modes. We also present evidence in support of this hypothesis.